THE IMPLEMENTATION OF THEME-BASED TEACHING IN IMPROVING STUDENTS' GRAMMAR SKILL : a quasi-experimental study in a junior high school in Lembang - Panjaitan, Sartika Permata Rosemary Br (2017)
Penelitian berjudul "Impelementasi Pengajaran Berbasis Tema dalam Meningkatkan Kemampuan Tata Bahasa Siswa" ini bertujuan untuk mencari tahu keefektifan pembelajaran berbasis tema dalam meningkatkan kemampuan tata bahasa siswa serta respon siswa terhadap tindakan yang diberikan. Dalam penelitian ini, dua tindakan diberikan guna dibandingkan. Maka dari itu penelitian kuasi eksperimental diadakan. Partisipan dalam penelitian ini ialah dua kelas yakni kelompok eksperimental dan kelompok kontrol. Lebih jauh lagi, pre-test dan posttest juga kuisioner dipilih sebagai instrument dalam penitian guna meraih data yang dibutuhkan. Hasil dari penelitian ini menunjukan bahwa pembelajaran berbasis tema mampu menunjukkan hasil yang signifikan terkait kemampuan tata bahasa siswa. Selain itu, respon siswa yang terlihat dari hasil kuisioner yang dibagikan menunjukkan hasil yang positif. Maka dari itu, implementasi pembelajaran berbasis tema ini efektif pada tingkat Sekolah Menengah Pertama terlebih dalam upaya meningkatkan kemampuan tata bahasa siswa.;---The study entitled "The Implementation of Theme-Based Teaching in Improving Students' Grammar Skill" was aimed to find out the effectiveness of theme-based teaching in improving students' grammar skill and the students' responses toward the treatment. In this study, two different treatments were given to be compared. Therefore, quasi-experimental was conducted. As the participants of the research, two classes were taken, namely experimental group and control group. Furthermore, pre-test, posttest and questionnaire was chosen as the instrument of the research in gaining the data. The result of the data demonstrated that theme-based teaching was able to exhibit statically significant result toward students' grammar skill. Moreover, the students' responses which are collected through the questionnaire revealed positive attitudes. Therefore, the implementation of theme-based teaching is effective in Junior High School especially in improving students' grammar skill.